The role of elastosonography, gray-scale and colour flow Doppler sonography in prediction of malignancy in thyroid nodules - Tatar, Idil Gunes (Radiol Oncol, 2014)
BACKGROUND: Ultrasound is as a noninvasive method commonly used in the work-up of thyroid nodules. This study aimed to evaluate the usefulness of sonographic and elastosonographic parameters in the discrimination of malignancy. PATIENTS AND METHODS. 150 thyroid nodules were evaluated by gray-scale, Doppler and elastosonography. The cytological analysis revealed that 141 nodules were benign and 9 were malignant. RESULTS: Orientation of the nodule was the only sonographic parameter associated with malignancy (p = 0.003). In the strain ratio analysis the best cut-off point was 1.935 to discriminate malignancy (p = 0.000), with 100% sensitivity, 76% specificity, 100% negative predictive value, 78.5% positive predictive value and 78% accuracy rate. There was a statistically significant correlation between the elasticity score and malignancy (p = 0.001). Most of the benign nodules had score 2 and 3, none of them displayed score 5. On the other hand, none of the malignant nodules had score 1 and 2, most of them displaying score 5. CONCLUSIONS: A change in the diagnostic algorithm of the thyroid nodules should be considered integrating the elastosonographic analysis.